Alberto P. Calderón. Theory of Potential and Singular Integrals. A Historical Perspective - Ortiz Fernández, Alejandro (2017)
This article is dedicated to give an historical critique vision about the contribution of the great mathematician Alberto P. Calderon on potential classical theory and on the singular integrals. In general, Calderon’s work was central in harmonic analysis in the second half of 20th Century because of it’s deepness, high originality andbeauty of his Works.